2018
DOI: 10.7196/samj.2018.v108i12.13422
|View full text |Cite
|
Sign up to set email alerts
|

Purpose-orientated stocking of procedure trolleys saves time in busy emergency centres

Abstract: HEALTHCARE DELIVERYPurpose-orientated stocking of procedure trolleys saves time in busy emergency centres P Furstenburg, MB ChB, Dip PEC (SA); A Oosthuizen, MB ChB, Dip PEC (SA), FCEM, MMed; L Wallis, MB ChB, MD, FRCEM, FCEM (SA) Background. Inefficient storage and sourcing of routinely required consumables located on procedure trolleys result in time wasted when preparing for common procedures in emergency centres (ECs), contributing to poor efficiency and quality of care. Objectives. We designed a novel purp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…The shortage of emergency drugs also impacts service response time and patient safety (18). Research by Furstenburg et al (2018) showed the importance of standardizing emergency trolleys in the ER. A standard emergency trolley will cut the time for providing necessary tools and medicines.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The shortage of emergency drugs also impacts service response time and patient safety (18). Research by Furstenburg et al (2018) showed the importance of standardizing emergency trolleys in the ER. A standard emergency trolley will cut the time for providing necessary tools and medicines.…”
Section: Discussionmentioning
confidence: 99%
“…A standard emergency trolley will cut the time for providing necessary tools and medicines. The shortened time will have an impact on the response to emergency services (19).…”
Section: Discussionmentioning
confidence: 99%